Victorious French after the siege of Rouen in 1449 (engraving, c. 1867) - A. Burgun (Wikimedia Commons, 1867)
Notice iconographique issue de Wikimedia Commons. Titre: Victorious French after the siege of Rouen in 1449 (engraving, c. 1867). Victorious French after the siege of Rouen in 1449 (engraving, c. 1867)
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons